Comparison of the hemolytic activity between C. albicans and non-albicans Candida species - Rodnei Dennis Rossoni; Junia Oliveira Barbosa; Simone Furgeri Godinho Vilela; Antonio Olavo Cardoso Jorge; Juliana Campos Junqueira (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The ability to produce enzymes, such as hemolysins, is an important virulence factor for the genus Candida.The objective of this study was to compare the hemolytic activity between C. albicansand non-albicans Candida species. Fifty strains of Candida species, isolated from the oral cavity of patients infected with HIV were studied. The isolates included the following species: C. albicans, C. dubliniensis, C. glabrata, C. tropicalis, C. krusei, C. parapsilosis, C. dubliniensis, C. norvegensis, C. lusitaniae, and C. guilliermondii. Hemolysin production was evaluated on Sabouraud dextrose agar containing chloramphenicol, blood, and glucose. A loop-full of pure Candidaculture was spot-inoculated onto plates and incubated at 37ºC for 24 h in a 5% CO2 atmosphere. Hemolytic activity was defined as the formation of a translucent halo around the colonies. All C. albicansstrains that were studied produced hemolysins. Among the non-albicans Candidaspecies, 86% exhibited hemolytic activity. Only C. guilliermondiiand some C. parapsilosis isolates were negative for this enzyme. In conclusion, most non-albicans Candidaspecies had a similar ability to produce hemolysins when compared to C. albicans.